2020
DOI: 10.1007/s11858-020-01196-0
|View full text |Cite
|
Sign up to set email alerts
|

Teaching with digital technology

Abstract: In this survey paper, we describe the state of the field of research on teaching mathematics with technology with an emphasis on the secondary school phase. We synthesize themes, questions, results and perspectives emphasized in the articles that appear in this issue alongside the relevant foundations of these ideas within the key journal articles, handbooks and conference papers. Our aim is to give an overview of the field that provides opportunities for readers to gain deeper insights into theoretical, metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(78 citation statements)
references
References 105 publications
1
67
0
10
Order By: Relevance
“…Drawing from this experience, the teacher fully agreed that Socrative application increases students' motivation. The SLT and technology-enabled learning work well together [33]- [36]. The lecturers need to ensure the content, collaboration, and communication in line with the digital technology they want to use in teaching and learning process [37]- [39].…”
Section: Motivationmentioning
confidence: 99%
“…Drawing from this experience, the teacher fully agreed that Socrative application increases students' motivation. The SLT and technology-enabled learning work well together [33]- [36]. The lecturers need to ensure the content, collaboration, and communication in line with the digital technology they want to use in teaching and learning process [37]- [39].…”
Section: Motivationmentioning
confidence: 99%
“…Hodgen and colleagues (Hodgen et al ( 2020 ) interviewed heads of departments in the UK and found that student–teacher interaction in mathematics teaching at distance was a concern. Clark-Wilson et al ( 2020 ) claimed that mathematics teachers in many countries were unprepared for online teaching. The Nesta ( 2020 ) report suggested that COVID led to continuing and even widening gaps between students in terms of their engagement and access to technology.…”
Section: Introductionmentioning
confidence: 99%
“…This is a limitation of our study, and an important direction for future research. Another limitation is that the design of the meta-resource took place before the COVID-19 crisis; thus, it did not take-into-account the strong impact of the crisis in terms of DT use and student autonomy (Clark-Wilson et al, 2020 ). Nevertheless, we claim that this study conducted in France has contributions both for research and for practice internationally; we present these in the conclusions.…”
Section: Discussionmentioning
confidence: 99%